2021
DOI: 10.3390/ani11020554
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Premating Calcium and Phosphorus Supplementation on Reproduction Efficiency of Grazing Yak Heifers

Abstract: Reproductive efficiency is the main factor limiting yak production on the Tibet Plateau. The purpose of this study was to investigate the effect of supplementation with calcium chloride (CaCl) and monocalcium phosphate (MCP) for 30 days before breeding on body weight (BW) change, serum bone metabolism biomarkers, conception rate, and calving rate of grazing yaks. Ninety 3 year old yak heifers (153.05 ± 6.56 kg BW) were assigned to three treatments (n = 30 per treatment): grazing without supplementation (CONT),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 55 publications
(65 reference statements)
0
5
0
1
Order By: Relevance
“…The level of Ca in the blood of Bali cattle reared in rice fields were also low due to consuming feed with low Ca (Pujiastari et al, 2015). Phosphorus is essential in bone mineralization and reproduction (Zhou et al, 2021). In this study, the availability of P in extensive rearing management was higher than intensive and semi-intensive.…”
Section: Adequacy Of Livestock Nutrition Feed Nutrientmentioning
confidence: 63%
See 1 more Smart Citation
“…The level of Ca in the blood of Bali cattle reared in rice fields were also low due to consuming feed with low Ca (Pujiastari et al, 2015). Phosphorus is essential in bone mineralization and reproduction (Zhou et al, 2021). In this study, the availability of P in extensive rearing management was higher than intensive and semi-intensive.…”
Section: Adequacy Of Livestock Nutrition Feed Nutrientmentioning
confidence: 63%
“…The low Ca consumption was due to the low Ca content in forage in oil palm plantation areas which was consumed in extensive rearing management (Table 4). Additional mineral intake is needed to meet the Ca requirement (Zhou et al, 2021). The highest P consumption in cattle was shown by extensive rearing management.…”
Section: The Consumption Of Feed Nutrientsmentioning
confidence: 99%
“…Since yaks are seasonal breeders with a high natural conception rate, the fertility of a yak herd is primarily influenced by the percentage of yak cows that return to estrus in the year of calving. Research conducted at Sichuan revealed that 78% of female herds became pregnant following their first service, 15% following the second, and 7% following the third or more ( 79 ). Moreover, puberty onset is significantly influenced by nutritional conditions and the rate of live weight increase, with faster-growing yak heifers experiencing it earlier ( 79 ).…”
Section: Reproduction and Breeding In Yaksmentioning
confidence: 99%
“…Research conducted at Sichuan revealed that 78% of female herds became pregnant following their first service, 15% following the second, and 7% following the third or more ( 79 ). Moreover, puberty onset is significantly influenced by nutritional conditions and the rate of live weight increase, with faster-growing yak heifers experiencing it earlier ( 79 ).…”
Section: Reproduction and Breeding In Yaksmentioning
confidence: 99%
“…O bovino tem capacidade de mobilizar fósforo dos ossos (e dos tecidos moles) quando a dieta é inadequada (30). Os microrganismos do rúmen parecem ser menos sensíveis que o hospedeiro à deficiência de P. Esta resistência devese provavelmente à eficiente reciclagem do elemento através da saliva e aos requisitos relativamente baixos dos microrganismos, embora, tanto reduções na síntese de proteína microbiana, como ineficiente degradação da fibra, tenham sido descritas pela deficiência deste elemento (31,32).…”
Section: Macromineraisunclassified